Manual dexterity and intralimb coordination assessment to distinguish different levels of impairment in boccia players with cerebral palsy - Roldan, A.; Sabido, R.; Barbado, D.; Caballero, C.; Reina, R. (Frontiers in Neurology, 2017)
Background: Boccia is a paralympic sport played by athletes with severe neurological impairments affecting all four limbs. Impaired manual dexterity (MD) and intralimb coordination (ILC) may limit individuals` ability to perform certain activities such as grasping, releasing, or manipulating objects, which are essential tasks for daily life or to participate in para sports such as boccia. However, there are currently no specific instruments available to assess hand-arm coordination in boccia players with severe cerebral palsy (CP).